Влияние каталитически активных покрытий на свойства газодиффузионного электрода - Тульский, Геннадий Георгиевич; Терещенко, Анастасия Артуровна; Тульская, Алена Геннадьевна; Березовский, Игорь Сергеевич (НТУ "ХПИ", 2016)
Исследован процесс электровосстановления кислорода до пероксида водорода в кислых растворах с применением газодиффузионного электрода. Скорость накопления пероксида водорода определяется в большей мере скоростью дальнейшего восстановления Н₂О₂ до воды, которая в свою очередь зависит от концентрации перекиси и катионов водорода в объеме электрода. Обоснован выбор материала рабочего электрода при электрохимическом синтезе Н₂О₂. Для исследований был выбран газодиффузионный электрод, состоящий из углеродного материала с нанесенным на его поверхность катализатором. В качестве каталитически активных покрытий в данной работе были использованы следующие материалы: RuO₂, MoO₃, WO₃ и активный углерод (АУ).

The process of electrochemical reduction of oxygen to hydrogen peroxide in acidic solutions with the use of electron-gas diffusion electrode. The rate of accumulation of hydrogen peroxide is determined to a greater extent the further recovery rate of Н₂О₂ to water which in turn, depends on the concentration of hydrogen peroxide and cations in the bulk of the electrode. The choice of the working electrode material in the electrochemical synthesis of Н₂О₂. Substantiated structure of gas diffusion electrode active coatings that provide the maximum reduction in electrode potential, its high electrical conductivity and durability. Substantiated structure of gas diffusion electrode active coatings that provide the maximum reduction in electrode potential, its high electrical conductivity and durability. For selected studies was a gas diffusion electrode composed of carbon material coated with catalyst on its surface. In the paper the following materials were used as catalytically active coating: RuO₂, MoO₃, WO₃ and active carbon (AC).
Influence catalytically active coating on the properties of the gas diffusion electrode
Keywords: газодиффузионный электрод; пероксид водорода; электрохимический синтез; катализатор; анодный процесс; активный углерод; gas diffusion electrode; hydrogen peroxide; electrochemical synthesis; catalyst; anodic process; active carbon